Asuhan Keperawatan Pada Pasien degan Congestive Heart Failure (CHF) di Ruang Jantung RSUP.Dr.Mdjamil padang - nur hasnah putri; Hilma Yessi; Debby Silvia Dewi; Linda Marni (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Congestive Heart Failure (CHF) is a condition in which the heart is unable to pump blood optimally to meet the body’s metabolic needs, resulting in impaired tissue perfusion and various complications. The World Health Organization states that cardiovascular disease is the leading cause of death worldwide, accounting for approximately 17.9 million deaths each year or about 32% of total global deaths. Based on data from the Kementerian Kesehatan Republik Indonesia in 2023, heart disease remains one of the major health problems in Indonesia with an increasing incidence rate. The purpose of this scientific paper is to provide nursing care for patients with Congestive Heart Failure (CHF), including assessment, nursing diagnoses, interventions, implementation, evaluation, and nursing documentation.The method used in this scientific paper was a case study approach using the nursing process on one patient, Mrs. N, in the cardiac inpatient ward at RSUP Dr. M. Djamil Padang from February 4–8, 2026. Data collection techniques included interviews, observation, physical examination, and documentation studies.The results of nursing care showed an improvement in the patient’s condition after five days of nursing interventions, indicated by improved blood pressure, reduced shortness of breath, decreased pain scale, and increased activity tolerance. It is expected that the patient will be able to perform optimal self-care through adherence to therapy, activity regulation, and the implementation of a healthy lifestyle in order to improve quality of life and prevent recurrence and further complications.